Islamic Mentoring at Masjid Syamsul Ulum: A Character-Building Strategy for Telkom University Students Based on HEI Values - Asdianur Hadi; Roni Nugraha; Nurmawan Nurmawan (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2025)
This article examines the mentoring program at Masjid Syamsul Ulum, Telkom University, as a model of Islamic character education based on campus mosques, integrated with the values of Harmony, Excellence, and Integrity (HEI) in a technology-based higher education environment. This study aims to describe the structure, implementation, and evaluation of the mentoring program, including its curriculum and its contribution to students' spiritual, social, and leadership competencies. The research employed a descriptive qualitative approach through document analysis (program proposals, modules, evaluation reports, and organizational statutes), complemented by student perception data collected via a questionnaire. The results indicate that the mentoring program at Masjid Syamsul Ulum is systematically designed with modules, measurable evaluation rubrics, and a sustainable mentor regeneration system, and is well-received by students. This integration has successfully internalized Islamic values while strengthening students' collaboration, soft skills, and social responsibility as digital native learners. In conclusion, the campus mosque mentoring program is proven to be strategic in supporting professional, adaptive Islamic character development and is worthy of replication in other universities.